Bouttios and late antique Antioch - Garstad, Benjamin. (Washington, DC)
xiii, 436 sayfa
Keywords: “This volume collects all that remains of the enigmatic late antique author Bouttios. On the basis of these fragments, Bouttios is identified as a Christian, placed in Antioch, and dated to the later fourth century - quite likely writing during the emperor Julian's stay in Antioch in 362-363. Bouttios's composition, a tendentious and didactic fiction that purported to be history, is further set in the context of fourth-century debates between pagans and Christians over the gods, luck, good government and kingship, and the characters of Constatine and Julian. After outlining the circumstances of Bouttios's life and work, the book then discusses specific topics that appear in the fragments. The account of the gods assigned to Bouttios is shown to be the culmination of both the critique of traditional theology developed within Greco-Roma philosophy and literature and the assault on the pagan pantheon by Christian apologists; virgin sacrifices said to accompany the founding of ancient cities are discussed with regard to the figure of Tyche (the goddess of luck), Christian's fraught relationship with her, and her role in ancient historiography. Finally, Bouttios's treatment of these sacrifices in particular and his work more generally and compared to the form, thought, and intention of modern conspiracy theories - situating his writing in what Richard Hofstadter termed 'the paranoid style.” --